Evaluation of Management of Closed Spinal Injury - Radhee, Haider K.; AbdulnabI, Ayad Yousif; Saed, Basim (AL-Kindy College Medical Journal, 2012)
Objectives: to evaluate the role of conservative, decompression, spine fixation in management of closed spinal injury. Methods: The study was conducted at Specialized Surgical hospital and Al-Kadhemayia Teaching Hospital, in the period between July 2003 and July 2005.The study included 61 patients categorized Into many groups according level of vertebral injury (cervical, cervicodorsal, dorsal, dorsolumbar, Lumbar and lumbosacral), type of injury (compressed fracture, burst fracture and fracture dislocation) And according the severity into three groups as G1( complete motor paralysis and sensory loss ) G2 ( complete motor paralysis and incomplete sensory loss) and G3 ( incomplete motor paralysis And incomplete sensory loss ).The methods of treatment include (conservative, decompression, And open reduction and internal fixation). Results: no deterioration of the neural function occurred in any case .All patients who had full neural Function on admission remained so. The patients who at time of admission was completely paraplegic Or tetraplegic did not show any neural improvement .Internal fixation was done to maintain good alignment of the spine and stabilize the fracture dislocation segment for early mobilization and rehabilitation no significant improvement in the neural status has occurred in patients with complete motor and sensory loss below the level of the injury at time of admission. The value of decompression of the spinal Canal may improve neurologic recovery or rate of recovery in some patients with an incomplete deficit. Conclusion: clinical awareness is the most important diagnostic point. Other associated injuries which frequently co-exist should not be forgotten. Adequate radiological examination must be done.MRI is very helpful especially in incomplete spinal cord injury. Conservative treatment consists of immobilization. Laminectomy was performed for patients who have incomplete neural deficit. Internal fixation Performed for patients who have fracture dislocation.